Epilepsy meets cancer: when, why, and what to do about it? - Weller, Michael; Stupp, Roger; Wick, Wolfgang (The lancet. Oncology, 2012)
Summary - The lifetime risk of having epileptic seizures is profoundly increased in patients with cancer: about 20% of all patients with systemic cancer may develop brain metastases. These patients and those with primary brain tumours have a lifetime risk of epilepsy of 20-80%. Moreover, exposure to chemotherapy or radiotherapy to the brain, cancer-related metabolic disturbances, stroke, and infection can provoke seizures. The management of epilepsy in patients with cancer includes diagnosis and treatment of the underlying cerebral pathological changes, secondary prophylaxis with antiepileptic drugs, and limiting of the effect of epilepsy and its treatment on the efficacy and tolerability of anticancer treatments, cognitive function, and quality of life. Because of the concern of drug-drug interactions, the pharmacological approach to epilepsy requires a multidisciplinary approach, specifically in a setting of rapidly increasing choices of agents both to treat cancer and cancer-associated epilepsy.
Gesehen am 16.05.2019